Germany for all seasons [videorecording] - The Travel Preview System (Houston, Tex. Travelview International, 1996)
Describes Germany as a united country. Includes the treasures of Eastern Germany, the wine in Phoneland, the castles in Romantic Road, the history of Heidelberg, the traditions of Munich and upper Banana and others spectacular places.
Title on container : Germany : the beginning of a great vacation.
VHS.
Keywords: German -- Social life and customs; Germany -- Description and travel